Knowledge as power: A critical analysis of Alvin Toffler’s perspective and its implications for developing economies - Nam, Ong Van (Edelweiss Applied Science and Technology, 2025)
In the contemporary global landscape, knowledge has emerged as a fundamental source of economic and political power, distinct from traditional power bases of violence and wealth. This study critically analyzes Alvin Toffler’s conceptualization of knowledge power and examines how it transforms social, economic, and political relationships during the transition to what Toffler termed the “Third Wave” civilization. Using a methodological framework grounded in dialectical materialism and textual analysis of Toffler’s key works, particularly Future Shock, The Third Wave, and Powershift, this research explores the evolution of his thinking on knowledge as the highest quality form of power. The findings indicate that Toffler’s perspective on knowledge power offers significant insights for developing economies like Vietnam, where the transition to a knowledge-based economy presents both opportunities and challenges. The study concludes that Toffler’s framework provides valuable theoretical foundations for understanding how developing nations can leverage knowledge power to accelerate economic development, though this requires strategic investments in education, information technology infrastructure, and research capabilities. This analysis contributes to both the theoretical discourse on power dynamics in the information age and practical policy considerations for countries navigating the transition to knowledge-based economies.